Gastrointestinal basidiobolomycosis: Beware of the great masquerade a case report. (2019) - Balkhair, A.; Al Wahaibi, A.; Al-Qadhi, H.; Al-Harthy, A.; Lakhtakia, R.; Rasool, W.; Ibrahim, S.
Highlights: We describe a previously healthy young patient with gastrointestinal basidiobolomycosis misdiagnosed as colonic malignancy. This is the first reported case in an adult patient from Oman suggesting that the disease is possibly under-recognized. Acquaintance with this exceptionally rare infection is critical for successful clinical outcome. Azoles are effective anti-fungal therapy for gastrointestinal basidiobolomycosis. Abstract: Basidiobolomycosis is rare infection caused by the saprophytic fungus Basidiobolus ranarum . Gastrointestinal basidiobolomycosis is an infrequent, albeit, increasingly reported, emerging form of the disease and typically affects immunocompetent individuals with potentially grave sequelae if unrecognized. Acquaintance with this exceptionally rare fungus and its potential for presenting as gastrointestinal mass masquerading as colonic malignancy is critical for timely diagnosis, appropriate treatment and successful clinical outcome. We report a case of gastrointestinal basidiobolomycosis masquerading as colonic malignancy in a 29-year-old Omani patient successfully treated with combination of surgery and prolonged azole antifungal therapy.